Pengaruh Faktor Pendidikan, Kemampuan Personel,Dan Dukungan Manajemen Puncak Terhadap Kinerja Sistem Informasi Akuntansi Pada CV. Kurogi Semarang - Uswatun Larasati; Subchan Subchan (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2021)
The purpose of this study was to analyze the effect of education, personnel capabilities and top management support on the performance of the CV accounting information system. Kurogi Semarang. The population in this study are all employees of CV. Kurogi Semarang, namely as many as 60 employees. The technique of determining the sample is purposive sampling method. The number of samples in this study were 40 employees. This research data analysis tool uses multiple linear regression. The results of the analysis show that education has a positive effect on the performance of accounting information systems. This is evidenced by the calculated t value which is greater than t table, namely 2.359 > 1.688, with a significant value of 0.024 <0.05. Personal ability has a negative effect on the performance of accounting information systems. This is evidenced by the t-count value that is greater than t-table, namely -2.421 (signed negative) > 1.688, with a significant value of 0.021 <0.05. Top management support has a positive effect on the accounting information system. This is evidenced by the t-count value that is greater than t-table, namely 4.467> 1.688, with a significant value of 0.000 <0.05.